Identification of Suitable Amalgamation with Resveratrol, Epigallocatechin-3-gallate, and Diallyl Trisulfide against Skin Cancer Cell Lines (A431) - Arumugam, Gobika; Yadav, Sangilimuthu Alagar (Indian Journal of Pharmaceutical Education and Research, 2024)
Introduction: Resveratrol, Epigallocatechin -3-gallate (EGCG) and Diallyl Trisulfide (DATS) are bioactive compounds in which two polyphenols and an organosulfur are naturally occurring bioactive chemicals that can be efficacious in skin cancer chemoprevention either independently or in combination. Objectives: Conglomerate analysis of RES, EGCG, and DATS was performed as a single and in binary combinations to investigate cancer cell viability, in vitro in the A431 (human epidermoid carcinoma) skin cancer cell line. Materials and Methods: Screening of cytotoxicity potential of bioactive combinations by MTT assay, nuclear fragmentation: Acridine orange / ethidium bromide AO/EtBr assay on skin cancer cell lines (A431). Results: Our result showed that the half-maximal growth inhibitory concentration for RES-(IC50)-42 μM/mL, EGCG (IC50)-44 μM/mL, and DATS (IC50)-36 μM/mL whereas the binary combination RES + EGCG (IC50)-20 μM/mL; EGCG + DATS (IC50)-13 μM/mL; DATS + RES (IC50)-24 μM/mL which is evident from the uptake of AO and EtBr dyes by live/dead cells. Conclusion: Amalgam of RES, EGCG, and DATS can succor to develop skin cancer treatment better than as a single. Compared to all the combinations EGCG + DATS possess higher anticancer potentials against A431 skin cancer cell line.
Keywords: Skin cancer; Synergistic effect of Resveratrol; Epigallocatechin-3-gallate; Diallyl; trisulfide; Dietary bioactive compound